The Egalitarian Principle of “Qist” as Lived Ethic: Towards a Liberational Tafsir - Omaima Mostafa Abou-Bakr (Religions, 2023)
The Qur’anic term and principle of “qist”—generally defined as fairness, equity, and giving each his/her due share—occurs twenty-two times and forms a particular intentional discourse against social and economic privilege and against power in its various dimensions. These occurrences, their contexts, and fields of meaning demonstrate its distinctive place within the Qur’anic moral worldview, at the nexus between private virtue ethics and collective praxis. Qist is presented not merely as an abstract ideal, but as a specific, concrete social and economic goal for the marginalized and disempowered of any community. Especially in the domains of gender relations, poverty conditions, and authorial power, the divine injunction for applying equality in lived contexts becomes a call for liberation from “zulm” (injustice) and “taghut” (false deities). Can the examination of this concept and its affiliates form the basis for a scriptural theorization on an Islamic theology of social and economic justice, of resistance to tyranny and unjust constructions of privilege and superiority? Towards an answer to this inquiry, one can argue that qist directs attention to the practical ways of applying the overarching, comprehensive value of shari’ah, al-‘adl (justice), as well as to its defining features of collectivity and distributiveness.